The Swedish consumer market for organic and conventional milk: A demand system analysis - Hanna Lindström (Institute of Retail Economics (HFI), 2021)
Increasing the production of organic food is becoming an important environmental target for many governments, and consumer demand for organic food is pivotal in reaching these targets. This paper studies consumer demand for organic and conventional milk, using weekly scanner data from the Swedish retail market for the years 2011–2017. Own- and cross-price elasticities of demand are estimated using a quadratic almost ideal demand system. While previous studies on this topic show that demand for organic milk is commonly more price elastic than for its conventional alternative, this paper complements previous literature by (i) studying a market with relatively small organic price premiums, (ii) using a highly representative sample of retailers, and (iii) differentiating between private labels and brands. Results show that demand for organic milk is relatively elastic, despite relatively small organic price premiums in the Swedish milk market. Results also show that demand for branded products is, generally, less elastic compared to private label products, suggesting that consumers have strong preferences for traditional, regional brands.
Keywords: D12; Q11; Q18; 330; Environmental policy analysis; Organic food policy; Demand system analysis